Examen especial al componente de bienes de larga duración del gobierno autónomo descentralizado del cantón paltas, provincia de Loja, periodo 01 de enero al 31 de diciembre del 2014 - Pogo Eras, Lady Maritza (2016)
The present titling work called "Special Examination of the Long-Term Assets Component of the Decentralized Autonomous Government of the Catón Paltas, Period from January 1 to December 31, 2014", was developed to fulfill a prerequisite to elect the title of Engineer in Accounting and Auditing Public Accountant Auditor at the National University of Loja. The objectives of the project were satisfactorily fulfilled, so as to give way to the development of the three phases of the present work: In the first part of the work a Bibliographic research was developed, through the consultation of Manuals, Norms, Laws, Books, Magazines and Other publications that correspond to the theme, with the aim of structuring a conceptual framework and reference, which helped to better understand the problem raised, there are concepts and definitions on the audit and special examination. The second part of the paper contains the results; Where it begins with a Work Order, Notification, so we also have the First Phase; As is the Planning, then the previous visit in which information is collected from the entity then we have the Preliminary Planning and Specific Planning, in the latter is presented the strategy to follow in the field work after having Evaluated the Control System Internal, whose results are recorded in the narrative cedulas; This is also the continuation of the Second Phase that refers to the execution of the field work, here the audit programs are developed, through a series of procedures that made possible the preparation of work papers that include the most important findings and thus Then gather sufficient and competent evidence that will serve to justify the legality of the administrative and financial operations considered for the correct acquisition, control and custody of the Long-lived Assets of the institution under examination. Then we have the Third Phase; Which is the communication of results which contains their respective comments, conclusions and recommendations to be seen in the final report of the special examination where it will allow the highest authority of the entity to make the best decisions in an efficient and timely manner for the correct control And custody of the assets owned by it.